Copper‐Catalyzed One‐Pot Denitrogenative–Dehydrogenative–Decarboxylative Coupling of β‐Ketoacids with Trifluorodiazoethane: Facile Access to Trifluoromethylated Aldol Products. Issue 27 (30th May 2014) - Xiong, Heng‐Ying; Yang, Zhen‐Yan; Chen, Zhen; Zeng, Jun‐Liang; Nie, Jing; Ma, Jun‐An
Abstract A novel copper‐catalyzed one‐pot cross‐coupling of β‐ketoacids with in situ generated trifluorodiazoethane has been developed. This reaction provides a direct and efficient method, in which one CC bond and one CO bond were formed in a carbenoid center with concomitant denitrogenation–dehydrogenation–decarboxylation, to afford trifluoromethylated aldol products. In several preliminary experiments, good to high enantioselectivities were also obtained.